General preparation method of organic solvent-free and template-free metal organic framework material

Through a solvent-free and template-free method, inorganic salts and organic ligands are reacted at high temperatures, and the water molecules in the hydrated salts are used as reaction media and structural guiding agents to solve the complex, time-consuming and environmentally polluting MOFs synthesis process of the existing MOFs. solve the problem and achieve efficient and environmentally friendly MOFs material preparation.

CN119350649APending Publication Date: 2025-01-24BEIJING UNIV OF TECH
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411572216.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-06
Publication Date
2025-01-24

AI Technical Summary

Technical Problem

The synthesis process of existing metal organic frames (MOFs) materials is complex and time-consuming. The use of toxic solvents leads to environmental pollution and high costs, making it difficult to adapt to large-scale industrial production.

Method used

The method of non -organic solvent and mold -free agent is used to grind the temperature of the inorganic salt with the organic ligand after mixing with the organic ligand, and then a high -temperature crystallization reaction in a closed container to obtain a solvent -free MOFS material. Water molecules in hydrophilic salts are used as reaction medium and structural orientation to help form an orderly MOF structure.

Benefits of technology

The simplified synthetic process is achieved, the crystallization time is shortened, the energy consumption is reduced, the use of toxic solvents is avoided, the production efficiency and the stability of materials are improved, and it is suitable for large -scale industrialized production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119350649A_ABST
    Figure CN119350649A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of crystalline materials, and particularly relates to a general preparation method of an organic solvent-free and template-free metal organic framework material. A series of porous MOFs are prepared by adopting a simple, green and efficient solvent-free method, and green synthesis of the metal organic framework crystal is realized under the condition of not adding an organic solvent and a template agent. The method is a universal MOF synthesis method, the crystallization time can be greatly shortened, the efficiency is high, the time is short, the cost is low, and the pollution is small.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of crystalline materials, and particularly relates to a general preparation method of a metal organic framework material without organic solvent or template agent. Background Art

[0002] Metal-organic frameworks (MOFs) are crystalline porous materials that are connected by metal ions or metal clusters and organic ligands through coordination bonds. They have the advantages of large specific surface area, adjustable pore size, and open metal sites. They are widely used in gas adsorption, storage, catalysis, sensing and other fields. As a versatile and widely used material, there are complex preparation processes in the synthesis process. Currently, they are mainly synthesized by solvent thermal method, that is, using different organic ligands and inorganic salts, N, N-dimethylformamide (DMF), N, N-dimethylacetamide (DMA), dimethyl sulfoxide (DMSO) as solvents, preparing a mixed solution, and heating and crystallizing in a reactor. This method is time-consuming and has low utilization rate of the reactor. In addition, these solvents are highly toxic, easily produce a large amount of waste liquid and have high synthesis costs, which is not conducive to large-scale industrial production and is prone to secondary pollution to the environment. In addition, low-valent state Therefore, it is particularly important to develop a green, efficient, clean and pollution-free synthesis route. Solvent-free synthesis cleverly avoids the use of toxic solvents, eliminates the steps of solvent addition, mixing, and treatment, simplifies the synthesis process, improves production efficiency, reduces energy consumption, and is easy to scale up and suitable for large-scale production, thus achieving the goals of reducing costs, safety, and environmental protection. In addition, solvent-free synthesis, due to the lack of direct participation of solvents, will produce some defects, increase surface area, improve catalytic performance, improve selectivity, enhance gas adsorption capacity, regulate optical properties, increase chemical diversity, and improve stability, etc., which has incomparable advantages over solvothermal synthesis. Summary of the invention

[0003] The purpose of the present invention is to provide a general preparation method of metal organic framework materials without organic solvents and template agents. The method improves and optimizes the synthesis methods of various metal organic frameworks (MOFs). The effect of rapid and green synthesis of MOFs by dry powder heating is achieved without adding any solvents and template agents.

[0004] The present invention is achieved through the following technical solutions: A general preparation method of a metal organic framework material without organic solvent and template agent comprises the following steps: The inorganic salt and the organic ligand are mixed and ground at room temperature. The ground mixture is placed in a sealed container and then subjected to a high-temperature crystallization reaction. The solid product after the reaction is taken out, cleaned and dried to obtain a solvent-free MOFs material.

[0005] Furthermore, the inorganic salt is a metal salt containing crystal water. The water molecules in the hydrated salt can serve as a reaction medium to provide the necessary environment for the coordination reaction between the metal ions and the organic ligands. In the absence of a traditional solvent, the water molecules in the hydrated salt can help maintain the fluidity of the reactants and promote the contact and reaction of the reactants; the water molecules in the hydrated salt can serve as a structure-directing agent to help guide the metal ions and organic ligands to arrange in a specific manner to form an ordered MOF structure.

[0006] Furthermore, the inorganic salt is a metal salt that does not contain water of crystallization. When the inorganic salt is a metal salt that does not contain water of crystallization, deionized water needs to be added into a sealed container.

[0007] The molar amount of deionized water added shall not exceed the molar amount of water in the hydrated metal salt of the same metal. For example, if the metal salt used is zirconium tetrachloride, in the form of zirconium oxychloride octahydrate, the molar amount of deionized water added shall not exceed eight times the molar amount of zirconium tetrachloride. Adding too much water will produce a gel, change the kinetics of the reaction, and make the nucleation and growth process of MOF slow or incomplete, resulting in the formation of a gel-like precursor instead of the expected crystal structure; it will also increase the solubility of the metal salt and the ligand, reduce the concentration of the metal salt and the ligand in the solution, thereby affecting the coordination reaction between the ligand and the metal ion, resulting in the formation of an amorphous or gel-like substance.

[0008] Furthermore, the inorganic salt is an aluminum salt containing crystal water. When the inorganic salt is an aluminum salt, an alkaline mineralizer needs to be added. Adding a base can deprotonate the ligand, and the deprotonated ligand is more likely to form a coordination bond with the aluminum ion; under alkaline conditions, the aluminum ion can form a stable complex with the hydroxide ion, and these complexes can serve as the active center for synthesizing MOF and are more likely to react with the metal salt.

[0009] Furthermore, the molar ratio of the organic ligand to the alkaline mineralizer is 1:(1-3). Excessive alkali may cause the already formed MOF structure to collapse, because the strong alkaline environment may destroy the coordination bonds of the MOF, causing its structure to collapse; excessive alkali will cause the pH value of the solution to be too high, which may exceed the optimal pH range for MOF synthesis, thus being unfavorable for the formation of MOF and may cause the coordination environment of the metal ions to change, forming species that are not suitable for coordination with the organic ligands.

[0010] The alkaline mineralizer is one or more of sodium hydroxide, potassium hydroxide and calcium hydroxide.

[0011] Furthermore, the organic ligand is a nitrogen-containing organic molecule or a polycarboxylic acid organic molecule having a multi-coordination ability.

[0012] Furthermore, the molar ratio of the inorganic salt to the organic ligand is 1:(1-3).

[0013] Furthermore, the grinding time is 5-20 min.

[0014] Furthermore, the crystallization reaction temperature is 80-150°C, and the crystallization time is 30min to 10h. At a lower temperature, it is just a simple physical mixing, lacking a bridge for the metal salt and the ligand to directly connect and react; at a higher temperature, the metal salt will be converted into an oxide, losing the original properties of the metal salt.

[0015] The beneficial technical effects of the present invention are as follows: The present invention innovatively adopts a simple, green and efficient solvent-free method to prepare a series of porous MOFs, and realizes the green synthesis of metal organic framework crystals without adding organic solvents and template agents. This method is a universal MOF synthesis method, which can be used to prepare a series of MOFs materials with different metals (low-priced divalent to high-priced tetravalent) and ligands. The method of the present invention can greatly shorten the crystallization time and reduce energy consumption. Therefore, it is highly efficient, short in time, low in cost, and low in pollution. It has the incomparable advantages of solvent heat and the prospect of realizing large-scale preparation and popularization. BRIEF DESCRIPTION OF THE DRAWINGS

[0016] Figure 1 The powder diffraction pattern and 77 K nitrogen adsorption pattern of MOF-801 obtained in Example 1.

[0017] Figure 2 The diffraction patterns of the powder samples obtained in Example 2 and Comparative Example 2.

[0018] Figure 3 The powder diffraction pattern and 77 K nitrogen adsorption pattern of MOF-804 obtained in Example 3 Figure 4 The powder diffraction pattern and 77 K nitrogen adsorption pattern of DUT-67 obtained in Example 4 are shown.

[0019] Figure 5 The powder diffraction pattern and 77 K nitrogen adsorption pattern of MIP-202 obtained in Example 5.

[0020] Figure 6 The following are the powder diffraction pattern and 77 K nitrogen adsorption pattern of HHU-1 obtained in Example 6.

[0021] Figure 7 The powder diffraction pattern and 77 K nitrogen adsorption pattern of CAU-61 obtained in Example 7 are shown.

[0022] Figure 8 The following are the powder diffraction pattern and 77 K nitrogen adsorption pattern of Aluminum fumarate obtained in Example 8.

[0023] Fig. 9 This is the diffraction pattern of the powder sample obtained in Comparative Example 2.

[0024] Fig.10 The powder diffraction pattern and 77 K nitrogen adsorption pattern of MOF-303 obtained in Example 9 are shown.

[0025] Fig.11 This is the powder diffraction pattern obtained in Comparative Example 3.

[0026] Fig.12 The powder diffraction pattern and 77 K nitrogen adsorption pattern of MIL-88B obtained in Example 10 are shown.

[0027] Fig.13 The Zn(AIP) powder diffraction pattern and 77 K nitrogen adsorption pattern obtained in Example 11 are shown.

[0028] Fig.14 The flame retardant properties of Zn(AIP) obtained in Example 11 and Zn(AIP) obtained in Comparative Example 4 on EP are compared. DETAILED DESCRIPTION

[0029] The present invention is further described below with reference to the embodiments.

[0030] Example 1 (MOF-801) 1. Analytically pure zirconium oxychloride octahydrate (ZrOCl2·8H2O) and fumaric acid were mixed in a molar ratio of 1:1, ground at room temperature for 5 min, and then transferred into a stainless steel reactor lined with polytetrafluoroethylene and crystallized at 120°C for 3 h.

[0031] 2. After the reactor is cooled, take out the solid product.

[0032] 3. Wash with deionized water and anhydrous ethanol three times respectively, filter and separate the solid, and dry it at 80 °C to finally obtain white MOF-801 powder.

[0033] The powder diffraction pattern and 77 K nitrogen adsorption obtained in Example 1 are shown in Figure 1 .

[0034] Example 2 (MOF-801) 1. Analytically pure zirconium tetrachloride (ZrCl4), fumaric acid and deionized water were mixed in a molar ratio of 1:1:4, ground at room temperature for 10 min, and then transferred into a stainless steel reactor lined with polytetrafluoroethylene and crystallized at 100 °C for 10 h.

[0035] 2. After the reactor is cooled, take out the solid product.

[0036] 3. Wash with deionized water and anhydrous ethanol three times respectively, filter and separate the solid, and dry it at 80 °C to finally obtain white MOF-801 powder.

[0037] The powder diffraction pattern obtained in Example 2 is shown in Figure 2 .

[0038] Comparative Example 1 (MOF-801) 1. Analytically pure zirconium tetrachloride (ZrCl4) and fumaric acid were mixed in a molar ratio of 1:1, ground at room temperature for 5 min, and then transferred into a stainless steel reactor lined with polytetrafluoroethylene and crystallized at 120 °C for 3 h.

[0039] 2. After the reactor is cooled, take out the solid product.

[0040] 3. Wash with deionized water and anhydrous ethanol three times respectively, filter and separate the solid, and dry it at 80°C to finally obtain a white powder.

[0041] The powder diffraction pattern obtained in Comparative Example 1 is shown in Figure 2 It can be seen that the characteristic peak of MOF-801 disappears. That is, when the metal salt used is not a hydrated salt, in the absence of water addition, the MOF-801 sample cannot be successfully obtained.

[0042] Example 3 (MOF-804) 1. Analytically pure zirconium oxychloride octahydrate (ZrOCl2·8H2O) and 2,5-hydroxyterephthalic acid were mixed in a molar ratio of 1:2, ground at room temperature for 10 min, and then transferred into a stainless steel reactor lined with polytetrafluoroethylene and crystallized at 130°C for 3.5 h.

[0043] 2. After the reactor is cooled, take out the solid product.

[0044] 3. Wash with deionized water and anhydrous ethanol three times respectively, filter and separate the solid, and dry it at 80 °C to finally obtain yellow MOF-804 powder.

[0045] The powder diffraction pattern and 77 K nitrogen adsorption of Example 3 are shown in Figure 3 .

[0046] Example 4 (DUT-67) 1. Analytically pure zirconium oxychloride octahydrate (ZrOCl2·8H2O) and 2,5-thiophenedicarboxylic acid were mixed in a molar ratio of 1:1, ground at room temperature for 18 min, and then transferred into a stainless steel reactor lined with polytetrafluoroethylene and crystallized at 120°C for 5 h.

[0047] 2. After the reactor is cooled, take out the solid product.

[0048] 3. Wash with deionized water and anhydrous ethanol three times respectively, filter and separate the solid, and dry it at 80°C to finally obtain white DUT-67 powder.

[0049] The powder diffraction pattern and 77 K nitrogen adsorption of Example 4 are shown in Figure 4 .

[0050] Example 5 (MIP-202) 1. Analytically pure zirconium oxychloride octahydrate (ZrOCl2·8H2O) and L-aspartic acid were mixed in a molar ratio of 1:1, ground at room temperature for 8 min, and then transferred into a stainless steel reactor lined with polytetrafluoroethylene and crystallized at 120 °C for 1.5 h.

[0051] 2. After the reactor is cooled, take out the solid product.

[0052] 3. Wash with deionized water and anhydrous ethanol three times respectively, filter and separate the solid, and dry it at 80°C to finally obtain white MIP-202 powder.

[0053] The powder diffraction pattern and 77 K nitrogen adsorption of Example 5 are shown in Figure 5 .

[0054] Example 6 (HHU-1) 1. Analytically pure zirconium oxychloride octahydrate (ZrOCl2·8H2O) and butynedicarboxylic acid were mixed in a molar ratio of 1:3, ground at room temperature for 20 min, and then transferred into a stainless steel reactor lined with polytetrafluoroethylene and crystallized at 90°C for 5 h.

[0055] 2. After the reactor is cooled, take out the solid product.

[0056] 3. Wash with deionized water and anhydrous ethanol three times respectively, filter and separate the solid, and dry it at 80 °C to finally obtain white HHU-1 powder.

[0057] The powder diffraction pattern and 77 K nitrogen adsorption of Example 6 are shown in Figure 6 .

[0058] Example 7 (CAU-61) 1. Analytically pure zirconium oxychloride octahydrate (ZrOCl2·8H2O) and pyromellitic acid were mixed in a molar ratio of 1:1, ground at room temperature for 15 minutes, and then transferred into a stainless steel reactor lined with polytetrafluoroethylene and crystallized at 120°C for 8 hours.

[0059] 2. After the reactor is cooled, take out the solid product.

[0060] 3. Wash with deionized water and anhydrous ethanol three times respectively, filter and separate the solid, and dry it at 80°C to finally obtain white CAU-61 powder.

[0061] The powder diffraction pattern and 77 K nitrogen adsorption of Example 7 are shown in Figure 7 .

[0062] Example 8 (Aluminum fumarate) 1. Analytically pure aluminum chloride hexahydrate (AlCl3·6H2O), fumaric acid and sodium hydroxide were mixed in a molar ratio of 1:1:1, ground at room temperature for 15 min, and then transferred into a stainless steel reactor lined with polytetrafluoroethylene and crystallized at 100°C for 7 h.

[0063] 2. After the reactor is cooled, take out the solid product.

[0064] 3. Wash with deionized water and anhydrous ethanol three times respectively, filter and separate the solid, and dry at 80°C to finally obtain white fumaric acid powder.

[0065] The powder diffraction pattern and 77 K nitrogen adsorption of Example 8 are shown in Figure 8 .

[0066] Comparative Example 2 (Aluminum fumarate) 1. Analytically pure aluminum chloride hexahydrate (AlCl3·6H2O) and fumaric acid were mixed in a molar ratio of 1:1, ground at room temperature for 5 min, and then transferred into a stainless steel reactor lined with polytetrafluoroethylene and crystallized at 120 °C for 5 h.

[0067] 2. After the reactor is cooled, take out the solid product.

[0068] 3. Wash with deionized water and anhydrous ethanol three times respectively, filter and separate the solid, and dry it at 80°C to finally obtain a white powder.

[0069] The powder diffraction pattern obtained in Comparative Example 2 is shown in Fig. 9 .

[0070] Example 9 (MOF-303) 1. Analytically pure aluminum chloride hexahydrate (AlCl3·6H2O), 3,5-pyrazoledicarboxylic acid, and sodium hydroxide were mixed in a molar ratio of 1:1:3, ground at room temperature for 10 min, and then transferred into a stainless steel reactor lined with polytetrafluoroethylene and crystallized at 120°C for 5 h.

[0071] 2. After the reactor is cooled, take out the solid product.

[0072] 3. Wash with deionized water and anhydrous ethanol three times respectively, filter and separate the solid, and dry it at 80°C to finally obtain a white powder.

[0073] The powder diffraction pattern and 77 K nitrogen adsorption of Example 9 are shown in Fig.10 .

[0074] Comparative Example 3 1. Analytically pure aluminum chloride hexahydrate (AlCl3·6H2O) and 3,5-pyrazoledicarboxylic acid were mixed in a molar ratio of 1:3, ground at room temperature for 20 min, and then transferred into a stainless steel reactor lined with polytetrafluoroethylene and crystallized at 120 °C for 5 h.

[0075] 2. After the reactor is cooled, take out the solid product.

[0076] 3. Wash with deionized water and anhydrous ethanol three times respectively, filter and separate the solid, and dry it at 80 °C to finally obtain white MOF-303 powder.

[0077] The powder diffraction pattern obtained in Comparative Example 3 is shown in Fig.11 .

[0078] It can be seen from Example 8 and Comparative Example 2 as well as Example 9 and Comparative Example 3 that when synthesizing aluminum-based MOF materials, if there is a lack of alkali, the MOF materials cannot be successfully synthesized.

[0079] Example 10 (MIL-88B) 1. Analytically pure ferric chloride hexahydrate (FeCl3·6H2O) and 2-aminoterephthalic acid were mixed in a molar ratio of 1:1, ground at room temperature for 15 min, and then transferred into a stainless steel reactor lined with polytetrafluoroethylene and crystallized at 95°C for 4 h.

[0080] 2. After the reactor is cooled, take out the solid product.

[0081] 3. Wash with deionized water and anhydrous ethanol three times respectively, filter and separate the solid, and dry it at 80°C to finally obtain light yellow MIL-88B powder.

[0082] The powder diffraction pattern and 77 K nitrogen adsorption of Example 10 are shown in Fig.12 .

[0083] Example 11 (F-Zn(AIP)) 1. Analytically pure zinc acetate dihydrate (Zn(CH3COO)2·2H2O) and 5-aminoisophthalic acid were mixed in a molar ratio of 1:1, ground at room temperature for 10 min, and then transferred into a tubular stainless steel reactor and crystallized at 90°C for 3 h.

[0084] 2. After the reactor is cooled, take out the solid product.

[0085] 3. Wash with deionized water and anhydrous ethanol three times respectively, filter and separate the solid, and dry it at 80°C to finally obtain white Zn(AIP) powder.

[0086] The powder diffraction pattern and 77 K nitrogen adsorption of Example 11 are shown in Fig.13 .

[0087] Comparative Example 4 (S-Zn(AIP)) 1. Zinc acetate dihydrate (0.0219 g, 0.1 mmol) and 5-aminoisophthalic acid (0.0181 g, 0.1 mmol) were dissolved in a mixed solvent of ethanol (4 mL), water (4 mL) and DMA (1 mL), and then the pH of the solution was adjusted to 5 with dilute nitric acid and stirred at room temperature for about 2 h to obtain a pink transparent solution. The solution was then added to a container and heated at 120°C for 3 days.

[0088] 2. After the reactor is cooled, take out the solid product.

[0089] 3. Wash with deionized water and anhydrous ethanol three times respectively, filter and separate the solid, and dry it at 80°C to finally obtain white Zn(AIP) powder.

[0090] The powder diffraction pattern obtained in Comparative Example 4 is shown in Fig.13 .

[0091] Application Example 1 As one of the most popular thermosetting polymers, epoxy resin (EP) is widely used in printed circuit boards, automobiles, ships, aerospace, and wind turbines due to its advantages such as excellent electrical insulation, good adhesion to fibers, cost-effectiveness, excellent chemical resistance, and dimensional stability. However, a key disadvantage of EP is its high flammability, which produces a large amount of suffocating smoke during combustion. Therefore, improving the fire resistance of EP in terms of smoke suppression and flame retardancy is a necessary condition to expand the scope of application.

[0092] By loading 2 wt % of F-Zn(AIP) and S-Zn(AIP) prepared in Example 11 and Comparative Example 4 in EP, cone calorimetry test was carried out. The flame retardant properties of Zn(AIP) / EP obtained in Application Example 1 were shown in FIG. Fig.14 , indicating that: compared with pure EP, the loaded F-Zn(AIP) is greatly improved, showing the performance advantage of solvent-free synthesis.

[0093] Example 12 (MIL-88B) 1. Mix analytically pure ferric chloride hexahydrate and 2-aminoterephthalic acid in a molar ratio of 1:1, grind at room temperature for 5 min, then transfer into a tubular stainless steel reactor and crystallize at 110 °C for 3 h.

[0094] 2. After the reactor is cooled, take out the solid product.

[0095] 3. Wash with deionized water and anhydrous ethanol three times respectively, filter and separate the solid, and dry it at 80°C to finally obtain the MIL-88B sample.

[0096] Example 13 (MUF-16) 1. Mix analytically pure cobalt acetate dihydrate and 5-aminoisophthalic acid in a molar ratio of 1:1, grind at room temperature for 15 min, then transfer into a tubular stainless steel reactor and crystallize at 100°C for 2 h.

[0097] 2. After the reactor is cooled, take out the solid product.

[0098] 3. Wash with deionized water and anhydrous ethanol three times respectively, filter and separate the solid, dry it at 80 °C, and finally obtain the MUF-16 sample.

[0099] Example 14 (MIL-101) 1. Analytically pure chromium nitrate nonahydrate and terephthalic acid were mixed in a molar ratio of 1:1, ground at room temperature for 5 min, and then transferred into a tubular stainless steel reactor and crystallized at 150 °C for 30 min.

[0100] 2. After the reactor is cooled, take out the solid product.

[0101] 3. Wash with deionized water and anhydrous ethanol three times respectively, filter and separate the solid, dry it at 80 °C, and finally obtain the MIL-101 sample.

[0102] Example 15 (ZIF-8) 1. Analytically pure zinc acetate dihydrate and benzopyrazole were mixed in a molar ratio of 1:1, ground at room temperature for 10 min, and then transferred into a tubular stainless steel reactor and crystallized at 120 °C for 50 min.

[0103] 2. After the reactor is cooled, take out the solid product.

[0104] 3. Wash with deionized water and anhydrous ethanol three times respectively, filter and separate the solid, and dry it at 80 °C to finally obtain the ZIF-8 sample.

[0105] Example 16 (ZIF-9) 1. Analytically pure cobalt nitrate hexahydrate and benzopyrazole were mixed in a molar ratio of 1:1, ground at room temperature for 5 min, and then transferred into a tubular stainless steel reactor and crystallized at 140 °C for 40 min.

[0106] 2. After the reactor is cooled, take out the solid product.

[0107] 3. Wash with deionized water and anhydrous ethanol three times respectively, filter and separate the solid, and dry it at 80 °C to finally obtain the ZIF-9 sample.

[0108] Example 17 (CPO-27) 1. Analytically pure nickel nitrate dihydrate and 2,5-hydroxyterephthalic acid were mixed in a molar ratio of 1:1, ground at room temperature for 8 min, and then transferred into a tubular stainless steel reactor and crystallized at 120 °C for 1 h.

[0109] 2. After the reactor is cooled, take out the solid product.

[0110] 3. Wash with deionized water and anhydrous ethanol three times respectively, filter and separate the solid, and dry it at 80°C to finally obtain a CPO-27 sample.

[0111] Example 18 (MOF-74) 1. Mix analytically pure magnesium acetate dihydrate and 2,5-hydroxyterephthalic acid in a molar ratio of 1:1, grind at room temperature for 15 minutes, and then transfer into a stainless steel reactor and crystallize at 130°C for 30 minutes.

[0112] 2. After the reactor is cooled, take out the solid product.

[0113] 3. Wash with deionized water and anhydrous ethanol three times respectively, filter and separate the solid, and dry it at 80 °C to finally obtain the MOF-74 sample.

[0114] Through the analysis of the above embodiments, it can be seen that the samples prepared in Examples 1-18 all have the characteristic diffraction peaks of MOFs and good N2 adsorption capacity, indicating that the template-free and solution-free method adopted in the present invention can obtain good MOFs skeleton structure crystals.

[0115] In summary, the method of the present invention can greatly shorten the crystallization time of MOF formation, and the specific surface area of ​​the obtained material is equivalent to that of the MOF material obtained by traditional solvent thermal synthesis. The method described in the present invention can successfully prepare a series of low-cost and high-cost MOFs materials. Therefore, the method in this application is a general synthesis method of MOF materials and is suitable for promotion and application.

Claims

1. A general method for preparing a metal organic framework material without organic solvent or template agent, characterized in that: The steps include: The inorganic salt and the organic ligand are mixed and ground at room temperature. The ground mixture is placed in a sealed container and then subjected to a high-temperature crystallization reaction. The solid product after the reaction is taken out, cleaned and dried to obtain a high-quality solvent-free MOFs material.

2. The general preparation method of the metal organic framework material without organic solvent and template agent according to claim 1, characterized in that: The inorganic salt is a metal salt containing crystal water.

3. The general preparation method of the metal organic framework material without organic solvent and template agent according to claim 1, characterized in that: The inorganic salt is a metal salt that does not contain water of crystallization. When the inorganic salt is a metal salt that does not contain water of crystallization, deionized water needs to be added into a sealed container.

4. The general preparation method of the metal organic framework material without organic solvent and template agent according to claim 1, characterized in that: The inorganic salt is an aluminum salt containing crystal water. When the inorganic salt is an aluminum salt, an alkaline mineralizer needs to be added.

5. The general method for preparing a metal organic framework material without organic solvent and template agent according to claim 4, characterized in that: The molar ratio of the organic ligand to the alkaline mineralizer is 1:(1-3).

6. The general method for preparing a metal organic framework material without organic solvent and template agent according to claim 1, characterized in that: The organic ligand is a nitrogen-containing organic molecule or a polycarboxylic acid organic molecule having a multi-coordination ability.

7. The general preparation method of the metal organic framework material without organic solvent and template agent according to claim 1, characterized in that: The molar ratio of the inorganic salt to the organic ligand is 1:(1-3).

8. The general method for preparing a metal organic framework material without organic solvent and template agent according to claim 1, characterized in that: The grinding time is 5-20min.

9. The general method for preparing a metal organic framework material without organic solvent and template agent according to claim 1, characterized in that: The crystallization reaction temperature is 80-150°C, and the crystallization time is 0.5-10h.

Citation Information

Patent Citations

  • Fluorine-free and solvent-free method for rapid synthesis of metal-organic framework material MIL-101(Cr)

    CN105061512A

  • Synthesis method of metal organic framework material

    CN113501965A

  • Low-cost rapid general green preparation method of stable metal organic framework material

    CN113667134A

  • Chromium-based metal organic framework material synthesized by solvent-free method as well as preparation method and application of chromium-based metal organic framework material

    CN118085316A